Free breakfasts in schools: design and conduct of a cluster randomised controlled trial of the Primary School Free Breakfast Initiative in Wales [ISRCTN18336527] - Hale Janine; Desousa Carol; Lynch Rebecca; Tapper Katy; Moore Graham F; Moore Laurence; Roberts Chris; Murphy Simon (BMC, 2007)
Abstract Background School-based breakfast provision is increasingly being seen as a means of improving educational performance and dietary behaviour amongst children. Furthermore, recognition is growing that breakfast provision offers potential as a means of addressing social inequalities in these outcomes. At present however, the evidence base on the effectiveness of breakfast provision in bringing about these improvements is limited. Methods/Design This paper describes the research design of a large scale evaluation of the effectiveness of the Welsh Assembly Government's Primary School Free Breakfast Initiative. A cluster randomised trial, with school as the unit of randomisation was used for the outcome evaluation, with a nested qualitative process evaluation. Quantitative outcome measures included dietary habits, attitudes, cognitive function, classroom behaviour, and school attendance. The study recruited 111 primary schools in Wales, of which 56 were randomly assigned to control condition and 55 to intervention. Participants were Year 5 and 6 students (aged 9-11 years) in these schools. Data were collected for all 111 schools at each of three time points: baseline, 4 month and 12 month follow-up. This was achieved through a repeated cross-sectional survey of approximately 4350 students on each of these occasions. Of those students in Year 5 at baseline, 1975 provided data at one or both of the follow-ups, forming a nested cohort. The evaluation also included a nested process evaluation, using questionnaires, semi-structured interviews and case studies with students, school staff, and local authority scheme coordinators as key informants. Discussion An overview of the methods used for the evaluation is presented, providing an example of the feasibility of conducting robust evaluations of policy initiatives using a randomised trial design with nested process evaluation. Details are provided of response rates and the flow of participants. Reflection is offered on methodological issues encountered at various stages through the course of the study, focusing upon issues associated with conducting a randomised trial of a government policy initiative, and with conducting research in school settings. Trial registration Current Controlled Trials ISRCTN18336527